Desenvolvimento e caracterização de uma mão robótica acionada por atuadores de liga com memória de forma - Silva, André Felipe Cavalcante (2015)
This work is based on studies that prove a great rejection rate by amputees on using prosthetic upper limbs due to various problems, such as weight, high noise and lack of anthropomorphism. In this context, this paper presents the development of a robotic hand drive which is not realized by conventional actuators, constituted of wires of a shape memory alloy (SMA). The mechanical structure of the robot hand was designed in CAD software and subsequently manufactured with ABS polymer through rapid prototyping using a three-dimensional printer. The project was designed partially based on the physiological characteristics of the human hand, regarding especially to the angles formed by fingers’ phalanges. A mechanical system was developed in order to compactly accommodate the thin wires of a NiTi SMA, known in this work as Artificial Muscle (AM) which made the compression of SMA wires easier. The performance (operation) of the fingers occurs by the AM activation that are connected to cables arranged in the lower part of the fingers’ structure, which, when activated, perform the movement of flexion. The return of each phalanx, or extension movement of the fingers occurs passively. Elastic elements were installed in the upper part of the phalanges which are responsible for this movement. To monitor the angles formed by each phalanx was used a resistive type sensor that is inserted inside it, varying its electric resistance according to angle variation. On top of this system, a fuzzy logic based controller was developed and it proved to be effective on monitoring the position of the robotic hand’s fingers. The performance of the robot hand can be considered appropriate, as it could partially achieve the desired angles based on the project design.